10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Accurate diagnosis of Lyme disease, caused by Borrelia burgdorferi, is essential for timely treatment and prevention of long-term complications. This study investigates discrepancies in widely used serological assays and their impact on diagnostic sensitivity in high-risk populations. We analyzed samples from an annual Lyme screening program conducted by Innatoss Laboratories between November 2020 and May 2022, targeting individuals with occupational exposure to ticks. A retrospective cohort of 60 positive serum samples from 57 participants (aged 23-64) was evaluated using three tier one protocols: EUROIMMUN/ZEUS ELISA, SERION ELISA, and Diasorin CLIA, followed by Viramed immunoblots for confirmation.Our findings revealed significant variability in test sensitivity: the EUROIMMUN/ZEUS protocol detected 96.8% of cases, compared to 84.1% for SERION (p = 0.023) and 69.8.0% for Diasorin (p<0.001). Notably, six recent Borrelia infections were missed due to test selection, as confirmed by longitudinal comparison with previous samples. One case study illustrated the clinical consequences of missed diagnoses, including delayed treatment and symptom persistence.These results underscore the need for standardized serological protocols and routine longitudinal sample comparison. We propose the establishment of a consensus panel to define assay performance criteria and recommend integration of electronic health records with laboratory systems to enable automated historical data retrieval. Adoption of more sensitive testing strategies and harmonized interpretation guidelines could significantly improve diagnostic accuracy and patient outcomes in Lyme disease.